Вплив конструкції оптичного кабелю на стабільність параметрів передавання - Захарченко, Николай Васильевич; Бондаренко, О. В. (Eastern-European Journal of Enterprise Technologies, 2009)
Considered provision to stabilities parameter issues of the optical cable (OK) with power element from steel wire to account of stability to designs of the cable to stretching effort, which depends on possible deformation. On base of the study of the criterion to possible deformation (the lengthening) OK, is offered optimum criterion, chosen on base characteristic become on border of the springy deformation of her(its) material.